2015
DOI: 10.1007/s00396-015-3641-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles induced micellar growth in sodium oleate wormlike micelles solutions

Abstract: The rheological behavior of anionic surfactant sodium oleate (NaOA) in the presence of inorganic salt of sodiu m c a r b o n a t e ( N a 2 C O 3 ) , o r g a n i c s a l t o f nOctyltrimethylammonium bromide (OTAB) and nano-sized silica particles (nano SiO 2 ) was studied in detail. Regardless of the surfactant concentration (NaOA), OTAB was stronger than that of Na 2 CO 3 in promoting the rapid growth of NaOA micelles, resulting in higher viscosity of NaOA aqueous solutions. It was found that nano SiO 2 nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…It was suggested that the WLMs are connected to surfactant layer on the particle surface by their end-caps because these parts are energetically less favorable in comparison with cylindrical central parts of the micelles. Similar results were obtained for silica nanoparticles oppositely charged with respect to WLMs [14,18]. At the same time, addition of particles into dense WLM network either decreased rheological properties or did not significantly alter them [14,18].…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…It was suggested that the WLMs are connected to surfactant layer on the particle surface by their end-caps because these parts are energetically less favorable in comparison with cylindrical central parts of the micelles. Similar results were obtained for silica nanoparticles oppositely charged with respect to WLMs [14,18]. At the same time, addition of particles into dense WLM network either decreased rheological properties or did not significantly alter them [14,18].…”
Section: Introductionsupporting
confidence: 82%
“…Similar results were obtained for silica nanoparticles oppositely charged with respect to WLMs [14,18]. At the same time, addition of particles into dense WLM network either decreased rheological properties or did not significantly alter them [14,18].…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Luo et al used barium titanate (BaTiO 3 ) nanoparticles to modify wormlike micelles by the anionic surfactant fatty acid methyl ester sulfonate sodium and investigated influence of different factors on the viscoelasticity of wormlike micelles, such as concentration of surfactant, mass fraction of nanoparticles, and temperature. Fan et al found that silica nanoparticles can induce micellar growth in NaOA (sodium oleate) wormlike micelles solutions, enhancing the bulk viscosity [ 23 ]. Pletneva et al have investigated novel viscoelastic smart suspensions based on cationic wormlike micelles with the addition of oppositely charged submicron magnetic particles [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…To solve this urgent problem, several research groups have proposed adding nanoparticles to enhance the viscoelasticity of wormlike micellar systems (Dai et al, ; Fei et al, ; Sambasivam et al, ). Fan et al analyzed the rheological properties of a system consisting of sodium oleate/octyltrimethyl ammonium bromide (NaOA/OTAB) and nanosilica (Fan et al, ). Compared with the pure micellar solution, the system with a moderate concentration of nanoparticles has a larger zero‐shear viscosity.…”
Section: Introductionmentioning
confidence: 99%